PROPOSED MARKETING STRATEGY FOR BALISTA CAFÃ - Lorenza, Aditya
Balista cafe is a business that specializes in culinary with the concept of Japanese food. They provide a variety of food menus such as sushi, takoyaki, ramen, milktea, dessert, and the archipelago menu. They can serve two types of customers, offline and online. Balista was founded in December 2014. Balista has been around for a long time in this cafe industry. They had had two branches, but now only one is left. Balista sales have recently declined. If Balista cannot attract more customers and increase their brand awareness, they will remain low-income, and also other competitors will pursue them. This situation has caused them to experience financial problems internally which will cause them to suffer losses. This study aims to help Balista analyze external and internal factors, SWOT analysis, and root cause analysis to establish the proposed strategy. From external and internal analysis, it was found that there are many opportunities and threats in the restaurant industry. It was also established that Balista had strengths and weaknesses to compete in the restaurant industry. External analysis must be combined with internal analysis to make a SWOT analysis. Root cause analysis is performed after the SWOT analysis is complete. In the root cause analysis, it shows that the reason Balista faces low sales, is because there is a change in Balista consumer behavior from offline to online. Based on the analysis of the place Balista is less attractive to be visited by visitors. The proposed strategy is made from the TOWS matrix analysis, which can divide alternative strategies from each of Balista's strengths, weaknesses, opportunities, and threats in the SWOT analysis. After analyzing the TOWS matrix, the researcher proposes a strategy to answer the main problem faced by Balista. The first strategy is to increase promotional activities through social media and paid promotions. The second strategy is to develop various package menus. The third strategy is to maximize cooperation with GoFood and Grabfood. The fourth strategy is to move to a smaller place.